ANALISIS FASA KRISTALIN PADA TULANG SAPI TIMOR DENGAN VARIASI WAKTU DAN TEMPERATUR PEMANASAN DENGAN PENGUJIAN XRD - raymundus rheymon soko; Erich U. K. Maliwemu; Dominggus G. H. Adoe (Universitas Nusa Cendana, 2025)
The aim of this research is to identify the crystalline phase of Timor cattle bone powder and characterize it using XRD (X-Ray Diffraction) testing. This research uses a method of analyzing the results of XRD (X-Ray Diffraction) of Timor beef bones with variations in heating time and temperature. After the beef bones have been ground, the sample is oven-treated for 1 and 2 hours at a temperature of 1000C, then 5 grams of the sample is taken for testing using XRD (X-Ray Diffraction). The research results show that a 1 hour time variation at a temperature of 100 0C has a purity level of 84.07% with a diameter of 32.81 mm, and a crystallinity of 85.1%. And a time variation of 2 hours at a temperature of 1000C has a purity level of 76.68% with a diameter of 31.97 nm, and a crystallinity of 98.0%.